News information : the organisation of press cuttings in the libraries of newspapers and broadcasting services - Whatmore, Geoffrey (Hamden, Conn. : Archon Books, 1965)
This must be one of the very few, if not the only talk to be given in this country for a long time on the classification of press cuttings.
Index and Bibliographical
aia 30/6/17
Loans
Keywords: Information science; Information science & librarianship; Newspaper office libraries